Cyclic direct simple shear testing of a Beaufort Sea clay - McCarron, W.O.; Lawrence, J.C.; Werner, R.J.; Germaine, J.T.; Cauble, D.F. (Canadian Geotechnical Journal, 1995)
Results are presented for undrained direct simple shear tests on a Beaufort Sea cohesive soil. Monotonic and one-way cyclic loading response characteristics are identified for a number of loading scenarios. The critical level of repeated loadings (CLRL) is determined for two overconsolidation ratios from tests having 30 000 cycles of loading. Postcyclic strength tests indicate that one-way cyclic loadings not causing failure have a strain-hardening effect on the material. High strain-rate testing is found to increase soil strength by as much as 40% compared with typical testing strain rates. Key words : strength, cyclic testing, clay, simple shear, strain rate.